2018
DOI: 10.1101/351387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-scale reconstructions of the mammalian secretory pathway predict metabolic costs and limitations of protein secretion

Abstract: 35Keywords 36 Metabolic network, secretory pathway, biotherapeutic production, systems biotechnology 37Indeed, recent studies have incorporated portions of the secretory pathway in metabolic models of yeast 55 3-5 . Furthermore, Lund and colleagues reconstructed a genetic interaction network of the mouse secretory 56 pathway and the unfolded protein response and analyzed it in the context of CHO cells 6 . However, such a 57 network does not encompass a stoichiometric reconstruction of the biochemical reactions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 93 publications
1
55
0
Order By: Relevance
“…In addition, it has recently been shown that depletion of a highly abundant mRNA encoding a non-essential protein can improve growth and product titer, indicating that it is possible to free up energetic and secretory resources by rational cell line engineering strategies 33 . This observation was supported by a model of the secretory pathway, which was able to accurately predict the increase in growth and protein productivity 19 . These studies have so far been limited to single engineering targets, but could easily be applied on a larger scale.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In addition, it has recently been shown that depletion of a highly abundant mRNA encoding a non-essential protein can improve growth and product titer, indicating that it is possible to free up energetic and secretory resources by rational cell line engineering strategies 33 . This observation was supported by a model of the secretory pathway, which was able to accurately predict the increase in growth and protein productivity 19 . These studies have so far been limited to single engineering targets, but could easily be applied on a larger scale.…”
Section: Discussionmentioning
confidence: 67%
“…A genome-scale model of protein secretion was adapted for use here 19 . Briefly, this model was adapted to focus on the bioenergetic costs of protein synthesis and translocation of each host-cell secreted protein.…”
Section: Quantification Of Secretome Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycosylation is a highly abundant and complex post-translational modification, decorating between one-fifth and one-half of eukaryotic proteins 1,2 . These diverse carbohydrates account for 12-25% of dry mass, and have important functional and pathological roles 3,4 . Despite their essentiality, glycans are difficult to study; thus, our understanding of their impact is limited.…”
Section: Introductionmentioning
confidence: 99%